Nuclear Disarmament and Non-Proliferation : Towards a Nuclear-Weapon free World? - Lodgaard, Sverre (New York Routledge Taylor and Francis Group, 2011)
"This book examines the current debate on nuclear non-proliferation and disarmament, notably the international non-proliferation regime and how to implement its disarmament provisions. Discussing the requirements of a new international consensus on nuclear disarmament and non-proliferation, this book builds on the three pillars of the nuclear non-proliferation treaty (NPT)
Includes Notes, References and Index.
Keywords: Nuclear Disarmament -- Nuclear Nonproliferation -- International Relations